Understanding Human–Technology Relations Within Technologization and Appification of Musicality - Tuuri, Kai; Koskela, Oskari (Frontiers in Psychology, 2020)
In this paper we outline a theoretical account of the relationship between technology and human musicality. An enactive and bio-cultural position is adopted that assumes a close coevolutionary relationship between the two. From this position we aim at clarifying how the present and emerging technologies, becoming embedded and embodied in our life-world, inevitably co-constitute and transform musical practices, skills, and ways of making sense of music. Therefore, as a premise of our scrutiny, we take it as a necessity to more deeply understand the ways that humans become affiliated to the ever-changing instruments of music technology, in order to better understand the coevolutionary impact on learning and other aspects of musicality being constituted together with these instruments. This investigation is particularly motivated by the rapid and diverse development of mobile applications, and their potential impact, as musical instruments, on learning and cognizing music. The term appification refers to enactive processes in which applications (i.e., apps) and their user interfaces, developed for various ecosystems of mobile smart technology, partake in re-organizing our ways of musical acting and thinking. On the basis of the theoretical analysis, we argue that understanding the phenomenon of the human-technology relationship, and its implications for our embodied musical minds, requires acknowledging (1) how apps contribute to conceptual constructing of musical activities, (2) how apps can be designed or utilized in a way that reinforces the epistemological continuum between embodied and abstract sensemaking, and (3) how apps become merged with musical instruments.